(untitled) (Indonesian Theological Justice Review, 2024)
Gender justice remains a significant challenge in Indonesia, with women often facing systemic discrimination in areas such as education, employment, and access to healthcare. This paper explores the role of theology in promoting gender justice, focusing on how religious traditions in Indonesia, including Islam, Christianity, and indigenous beliefs, address women’s rights. By analyzing religious texts, theological teachings, and interpretations, the study examines how religious leaders and scholars frame gender roles, women’s empowerment, and gender-based violence within the context of justice. The paper highlights theological perspectives that support gender equality, such as Islamic teachings on women’s rights to education and economic independence, and Christian views on the equality of men and women in Christ. It also considers how certain theological interpretations may perpetuate gender inequality and contribute to cultural norms that disadvantage women. The research emphasizes the need for religious communities to engage in reinterpreting sacred texts and traditions in ways that support gender justice and equality. The study argues that religious leaders and institutions have the potential to play a key role in advancing gender justice by promoting inclusive interpretations of scripture and advocating for legal reforms that protect women’s rights. Recommendations include encouraging interfaith collaboration on gender issues, strengthening women’s leadership in religious communities, and promoting gender-sensitive theological education.